The Home Visit Rating Scales: Revised, restructured, and revalidated. Issue 3 (1st April 2019) - Roggman, Lori A.; Cook, Gina A.; Innocenti, Mark S.; Jump Norman, Vonda K.; Boyce, Lisa K.; Olson, Tasha L.; Christiansen, Katie; Peterson, Carla A.
ABSTRACT: The Home Visit Rating Scales (HOVRS) were initially developed from field‐based descriptions of successful home visits and are supported by home‐visiting research in multiple disciplines. Four home‐visiting practices scales include indicators of relationship building with families, responsiveness to family strengths, facilitation of parent–child interaction, and collaboration with parents. Three family engagement scales include indicators of parent–child interaction, parent engagement, and child engagement in the visit. The original version, the HOVRS‐1, was validated using video and data from two Early Head Start home‐visiting programs. Conceptual and structural changes for the HOVRS‐3 were designed to improve readability, usability, and clarity. Newly trained observers used the HOVRS‐3 to observe archived videos from the original measurement sample. The HOVRS‐3 showed good interrater reliability, scale internal consistency, convergent validity, predictive validity, practical significance, and version stability. When the HOVRS‐3 home‐visit quality scores were higher, it was twice as likely for parenting scores to be average or better and for child language to be at age level or better at age 3 years, over and above parenting and child language at age 1 year. The HOVRS can guide observations of home‐visit quality in infant–toddler and early childhood programs to improve home‐visiting practices and family engagement.